A magyar védelmi ipar újraépítése Trianon és 2010 után – a két világháború között zajló haderőfejlesztés és a Zrínyi Honvédelmi és Haderőfejlesztési Program összevetése - Szabó, Zoltán Tamás; Forgó, Gábor; Alpek, B. Levente (Közép-Európai Közlemények, 2023)
The article aims to provide a review about the main arguments regarding the Hungarian military development between the two world wars, and the Zrínyi National Defence and Force Development Program, which started in the 2010s and is still in progress. To highlight which goals and concepts they operate, what resources they are based on, and what economic and geopolitical consequences they create(d). Furthermore, we examine the state of the military and defense industry before the two military development programs, as well as the geopolitical situation and tensions surrounding the two military development programs and the main trends of the international defense industry, and we place the military development programs in relation to international trends. Due to the historical embedding of the topic and the consequences of the Trianon Peace Edict, we begin the study with a historical overview, in which we review the defense capabilities of the Austro-Hungarian Monarchy and especially the Kingdom of Hungary within. We will then briefly outline the background of the Hungarian collapse and the loss of the country after the First World War, as well as briefly deal with the National Army, which was the remainder of the nation's armed forces and formed the basis of the later Royal Hungarian Armed Forces, and the Hungarian free forces that succesfully fought for the referendum of Sopron to be held. We also deal in detail with the restrictions of the treaty of Trianon and the period of concealment (hiding of military hardware and units), which largely determined the conditions and starting position of the military development between the two world wars. Overall, it can be stated that the domestic military development program launched in the 1930s achieved significant results compared to the circumstances, but the rapid outbreak of the Second World War and the international environment did not favor it. International trends already showed an increase in defense spending from the beginning of the 1930s, which means that Hungary joined the trend with considerable delay. On the other hand, it currently seems that the announcement of the Zrínyi National Defence and Force Development Program preceded the upward trend in international defense spending by about five years. Indeed, defense spending in proportion to global GDP started to increase again from 2019, and the military development program of Germany has been announced in 2022. A tanulmány célja áttekinteni, hogy a két világháború között zajló magyar haderőfejlesztés, illetve a 2010-es években induló és ma is zajló Zrínyi Honvédelmi és Haderőfejlesztési Program milyen célrendszerrel és koncepciókkal operál, milyen erőforrásokra épül és milyen gazdaság- és geopolitikai következményeket teremt. Továbbá megvizsgáljuk a haderő és védelmi ipar állapotát a két haderőfejlesztési program előtt, valamint a két program körüli geopolitkai helyzetet és a nemzetközi védelmi ipari trendeket és elhelyezzük a haderőfejlesztési programokat a nemzetközi trendek viszonylatában. A téma történelmi beágyazottsága és a trianoni békediktátum máig ható következményei miatt a tanulmányt egy történelmi áttekintéssel kezdjük, amelyben az Osztrák-Magyar Monarchia és azon belül a Magyar Királyság védelmi képességeit tekintjük át. Majd röviden felvázoljuk az első világháború utáni magyar összeomlás és az ország elvesztésének a hátterét, valamint röviden foglalkozunk a nemzet fegyveres erejének maradékát jelentő és a későbbi Magyar Királyi Honvédség alapját képező Nemzeti Hadsereggel és a soproni népszavazást kiharcoló magyar szabadcsapatokkal. A két világháború közötti haderőfejlesztés feltételeit és kiindulási pozícióját nagyban meghatározó trianoni korlátozásokkal és a rejtés időszakával is részletesen foglalkozunk. Összességében elmondható, hogy az 1930-as években induló hazai haderőfejlesztési program a körülményekhez képest jelentős eredményeket ért el, azonban a második világháború gyors kitörése és a nemzetközi környezet nem kedvezett neki. A nemzetközi trendek ugyanis már az 1930-as évek elejétől a védelmi kiadások emelkedését mutatták, vagyis Magyarország jelentős késéssel csatlakozott a trendhez. Ezzel szemben, jelenleg úgy tűnik, a Zrínyi Honvédelmi és Haderőfejlesztési Program meghirdetése mintegy öt évvel megelőzte a nemzetközi védelmi kiadások emelkedő trendre történő fordulását. A globális GDP-arányos védelmi kiadások ugyanis 2019-től kezdtek újra növekedni, a német haderőfejlesztési programot pedig 2022-ben hirdették meg.